Transmission dynamics of MERS-CoV in a transgenic human DPP4 mouse model - Neeltje van Doremalen; Trenton Bushmaker; Robert J. Fischer; Atsushi Okumura; Dania M. Figueroa Acosta; Rebekah J. McMinn; Michael Letko; Dana Scott; Greg Saturday; Vincent J. Munster (npj Viruses)
Abstract Since 2002, three novel coronavirus outbreaks have occurred: severe acute respiratory syndrome coronavirus (SARS-CoV-1), Middle East respiratory syndrome coronavirus (MERS-CoV), and SARS-CoV-2. A better understanding of the transmission potential of coronaviruses will result in adequate infection control precautions and an early halt of transmission within the human population. Experiments on the stability of coronaviruses in the environment, as well as transmission models, are thus pertinent. Here, we show that transgenic mice expressing human DPP4 can be infected with MERS-CoV via the aerosol route. Exposure to 5 × 106 TCID50 and 5 × 104 TCID50 MERS-CoV per cage via fomites resulted in transmission in 15 out of 20 and 11 out of 18 animals, respectively. Exposure of sentinel mice to donor mice one day post inoculation with 105 TCID50 MERS-CoV resulted in transmission in 1 out of 38 mice via direct contact and 4 out of 54 mice via airborne contact. Exposure to donor mice inoculated with 104 TCID50 MERS-CoV resulted in transmission in 0 out of 20 pairs via direct contact and 0 out of 5 pairs via the airborne route. Our model shows limited transmission of MERS-CoV via the fomite, direct contact, and airborne routes. The hDPP4 mouse model will allow assessment of the ongoing evolution of MERS-CoV in the context of acquiring enhanced human-to-human transmission kinetics and will inform the development of other transmission models.